Dual red and near-infrared light-emitting diode irradiation ameliorates LPS-induced otitis media in a rat model - Ko, Yoo-Seung; Gi, Eun-Ji; Lee, Sungsu; Cho, Hyong-Ho (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Otitis media (OM) is an infectious and inflammatory disease of the middle ear (ME) that often recurs and requires long-term antibiotic treatment. Light emitting diode (LED)-based devices have shown therapeutic efficacy in reducing inflammation. This study aimed to investigate the anti-inflammatory effects of red and near-infrared (NIR) LED irradiation on lipopolysaccharide (LPS)-induced OM in rats, human middle ear epithelial cells (HMEECs), and murine macrophage cells (RAW 264.7). Methods: An animal model was established by LPS injection (2.0 mg/ml) into the ME of rats via the tympanic membrane. A red/NIR LED system was used to irradiate the rats (655/842 nm, intensity: 102 mW/m2, time: 30 min/day for 3 days and cells (653/842 nm, intensity: 49.4 mW/m2, time: 3 h) after LPS exposure. Hematoxylin & eosin staining was performed to examine pathomorphological changes in the tympanic cavity of the ME of the rats. Enzyme-linked immunosorbent assay, immunoblotting, and RT-qPCR analyses were used to determine the mRNA and protein expression levels of interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α). Mitogen-activated protein kinases (MAPKs) signaling was examined to elucidate the molecular mechanism underlying the reduction of LPS-induced pro-inflammatory cytokines following LED irradiation. Results: The ME mucosal thickness and inflammatory cell deposits were increased by LPS injection, which were reduced by LED irradiation. The protein expression levels of IL-1β, IL-6, and TNF-α were significantly reduced in the LED-irradiated OM group. LED irradiation strongly inhibited the production of LPS-stimulated IL-1β, IL-6, and TNF-α in HMEECs and RAW 264.7 cells without cytotoxicity in vitro. Furthermore, the phosphorylation of ERK, p38, and JNK was inhibited by LED irradiation. Conclusions: This study demonstrated that red/NIR LED irradiation effectively suppressed inflammation caused by OM. Moreover, red/ NIR LED irradiation reduced pro-inflammatory cytokine production in HMEECs and RAW 264.7 cells through the blockade of MAPK signaling.